Differential effect of thermal stress on HSP70 expression, nitric oxide production and cell proliferation among native and crossbred dairy cattle. (July 2016) - Bhanuprakash, V.; Singh, Umesh; Sengar, Gyanendra; Sajjanar, Basavaraj; Bhusan, Bharat; Raja, T.V.; Alex, Rani; Kumar, Sushil; Singh, Rani; Ashish Kumar,; Alyethodi, R.R.; Kumar, Suresh; et al.
Abstract: In a tropical country like India, thermal stress is one of the major factors which significantly affects the productivity of dairy cattle. The present study was aimed to identify the effect of heat and cold stress on cell viability, mitogen stimulation indices, nitric oxide production and HSP70 expression in Sahiwal and Holstein crossbred (Frieswal) population in India. The results indicated that the Sahiwal breed can better withstand the effect of heat and cold stress significantly (P<0.05) when compared to the crossbred cattle due to the higher survivability of the Peripheral Blood Mononuclear Cells (PBMCs) and Phytohemagglutinin (PHA-P) mitogen based stimulation indices. The study also revealed the significant differences (P<0.05) in the level of nitric oxide (µM) production amongst the pre and post thermal stressed samples of Sahiwal and Frieswal crossbred samples. Further, the expression of HSP70 was significantly (P<0.05) higher in Sahiwal compared to Frieswal immediately after heat/cold shock to 6 h of recovery as indirect ELISA analysis showed gradual rise in the Hsp70 protein concentration (ng/ml) immediately after heat and cold stress (0 h) and reached the peak at 6 h of recovery. Western blot and immune fluorescent assay results were also corroborated with the findings of indirect ELISA. In Sahiwal cattle the mRNA expression of HSP70 and its protein concentration were higher (P<0.05) during peak summer (44 °C) and winter (10 °C) as compared to Frieswal cattle. This investigation supports the earlier information on the higher adaptability of indigenous cattle breeds to hot and humid conditions compared to the crossbreds of temperate cattle breeds. Highlights: Survival of PBMCs and cell proliferation were significantly (P<0.05) higher in Sahiwal than Frieswal after thermal stress. NO level at micro molar concentration was significantly lower (P<0.05) both at pre and post thermal stressed groups. HSP70 mRNA and protein concentration were significantly (P<0.05) higher in Sahiwal than Frieswal.